Differentiation of Green Taxes: A Political-Economy Analysis for Germany - Niels Anger; Christoph Böhringer; Andreas Lange (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
In this paper we study political-economy determinants of the differentiation of environmental taxes between sectors. Using a common-agency model, we provide predictions on tax differentiation which are then tested using data from the German Ecological Tax Reform. As the reform is revenue neutral and reduces labor costs, tax differentiation is not only determined by the activity of lobby groups favoring reduced tax rates, but also by the groups? interest in revenue rebates to labor. Empirical data underpin our theoretical findings: A regression analysis of Germany?s green tax reform explains environmental tax differentiation by the presence of sectoral interest groups. Besides market concentration and energy demand elasticities, the exposure of industries to international trade flows plays an important role in the environmental tax design.
Keywords: P16; H23; D62; 330; environmental tax reform; interest groups; common agency; Ökosteuer; Steuerreform; Arbeitskosten; Interessenpolitik; Branche; Schätzung; Deutschland